A Study on Socio-Demographic Profile and Risk Factors Present in HIV Infected Patients Attending Art Centre in Tertiary Care Hospital in Rajasthan, India - Baig , Vaseem N; Swarnkar , Madhusudan; Bhardwaj , Ashok K; Rathore , Monika; Kasyap , Amita (National Journal of Community Medicine, 2012)
Background: Globally India is leading in the world as far as numbers of HIV positive cases, and there is paucity of studies related to socio-demographic profile of HIV/AIDS patients in Rajasthan. Methodology: This socio-demographic study was conducted on HIV patients attending ART centre of SMS hospital, Jaipur (Rajasthan). At the time of study, 247 patients were registered however study was done on 200 cases. Data collection was done by personal Interview and from case record. Results: Most of the study individuals (97%) belonged to the age group 15-49 years, 73.5% were males & 26.5% were females. Majority of the study individuals were Hindus (91%) and married (75.50%). Unprotected sexual route was the most common (91.5%) mode of transmission; among which heterosexual route was found to be the commonest (95.62%). Most common first presenting complaint was fever (58.50%). Conclusion: Most of HIV positive cases belonged to the sexually active & economically productive age group, low socioeconomic status, rural area and the sexual route is the predominant mode of transmission.